2019
DOI: 10.1002/cam4.2789
|View full text |Cite
|
Sign up to set email alerts
|

High serum PD‐L1 level is a poor prognostic biomarker in surgically treated esophageal cancer

Abstract: Background Programmed death ligand 1 (PD‐L1) inhibitor has been approved as one of the standard therapies for various cancers. Some reports have shown that serum PD‐L1 level is associated with advanced tumor stages and poor prognosis; however, corresponding pathological information in esophageal cancer patients is lacking. Therefore, we evaluated the clinicopathological and prognostic impact of serum PD‐L1 levels in surgically treated esophageal cancer. Methods A total of 150 patients who underwent radical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…The results obtained showed that cats presenting mammary carcinoma subtypes associated with more aggressive features and poor prognosis [ 31 ] (HER2-positive and TN normal-like) displayed significantly increased serum PD-1 and PD-L1 levels, as reported in humans with HER2-positive metastatic breast cancer [ 32 ], TN breast cancer [ 23 ], renal cell carcinoma [ 25 ], esophageal cancer [ 33 ], gastric cancer [ 24 ], advanced pancreatic cancer [ 34 ], lung cancer [ 35 ] and metastatic melanoma [ 36 ] correlated to shorter overall survival and tumor-free survival times [ 23 , 25 , 32 , 33 , 35 ], suggesting a conserved role of the PD-1/PD-L1 axis in both species. Moreover, as reported in humans, our findings uncovered a positive correlation between serum PD-1 and PD-L1 levels, suggesting that both molecules are co-regulated [ 23 , 34 ].…”
Section: Discussionmentioning
confidence: 97%
“…The results obtained showed that cats presenting mammary carcinoma subtypes associated with more aggressive features and poor prognosis [ 31 ] (HER2-positive and TN normal-like) displayed significantly increased serum PD-1 and PD-L1 levels, as reported in humans with HER2-positive metastatic breast cancer [ 32 ], TN breast cancer [ 23 ], renal cell carcinoma [ 25 ], esophageal cancer [ 33 ], gastric cancer [ 24 ], advanced pancreatic cancer [ 34 ], lung cancer [ 35 ] and metastatic melanoma [ 36 ] correlated to shorter overall survival and tumor-free survival times [ 23 , 25 , 32 , 33 , 35 ], suggesting a conserved role of the PD-1/PD-L1 axis in both species. Moreover, as reported in humans, our findings uncovered a positive correlation between serum PD-1 and PD-L1 levels, suggesting that both molecules are co-regulated [ 23 , 34 ].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have reported that patients with a higher expression of PD-L1 in cancer cells are correlated with preferential outcome in lung cancer (13). However, others have found that a high PD-L1 expression level is a poor prognostic factor in esophageal and cervical cancers (14,15). Although recent studies have been carried out (16)(17)(18), the association between the clinical response to anti-PD-1 antibodies and PD-L1 expression in HCC tumor cells remains unclear.…”
Section: Original Articlementioning
confidence: 99%
“…Regarding biomarker, we recently reported about PD-L1, which is a poor prognostic biomarker in esophageal cancer ( 4 ). Unexpectedly, in the present study, PD-L1 correlated positively with favorable-prognosis-associated s-PCSK9-Ab levels ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each clinicopathological feature and prognosis of these patients was examined. The cutoff level of serum PD-L1 was set at 75 percentile (65.6 pg/mL) of esophageal cancer ( 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation